Optimisation of Extraction Methods and Flavour Profiling of Redclaw (Cherax Quadricarinatus) Crayfish - Zayapor, Mohd Nazri (2005)
Redclaw crayfish (Cherax quadricarinatus) is native to Australia and was introduced to Malaysia in the past few years. This study on the Redclaw crayfish flavour extract was carried out at three different stages with the respective objectives: 1) screening stage; to determine a suitable extraction condition, 2) flavour profile comparison with the commercial flavourings; to find the similarities of flavour profile of Redclaw extract with the commercial flavourings, and 3) identification of aromatic compounds; to determine the aroma profile in Redclaw aqueous extract and cooked crayfish. At the screening stage, different extraction conditions vis. simmering time (10 - 40 min) and temperature (65 - 95OC), Redclaw-water ratio (4 - 6), and salt concentration (1 - 10%) was carried out for head, tail and claws. Total amino acids (> 10 mgg-') and taste amino acids (glutamic acid, glycine and alanine) (> 5 mgg-' of the total three amino acids) were chosen as the indicators of the flavour quality. Principal Component Analysis (PCA) was used to study the pattern of amino acid distributions. It was found that extraction conditions at salt concentration of less than 5.5%; water ratio of less than 5; simmering time and temperature of less than 30 min and 80°C, respectively produced more taste amino acids (> 5 mgg-' in total) in all extracts. In general, longer simmering time significantly (pc0.05) produced more bitter amino acids, whereas shorter time ( ~ 3 0m in) resulted in higher distribution of sweet and umami-precursor amino acids. Bitter amino acids increased as the temperature increased above 90°C. Salt concentration and Redclaw-water ratio (wlv) did not give significant affect on the distribution of amino acids in any body-part. At the comparison stage, amino acids, 5' mononucleotides, soluble sugars, and organic acids were chosen as the taste-active component quality indicators. PCA was also used to determine the similarities of Redclaw extract (EXT) with the selected commercial flavourings. EXT produced at 85OC for 30 min with 5.0% salt and Redclaw-water ratio of 1:2 (wlv) was used in this study. It had relatively lower taste-active components than the selected commercial flavourings. PCA showed that EXT has similar amino acid profiles to shrimp paste and fish sauce in particular that of glutamic acid and was also similar to fish sauce in its 5' uridine monophospate (UMP) and 5' cytidine monophospate (CMP) content. Redclaw extract concentrate (RCE) produced has an earthy and cooked cabbage-like, however, less fishy and seafood-like aroma than all commercial flavourings. Aroma identification of aqueous extract was carried out at pH 7.8, 6.4 and 4.6; while cooked Redclaw was maintained at its original pH to determine the effect of pH on aroma profile. At pH 7.8, 6.4 and 4.6, a total of 82, 44 and 46 aromatic compounds were identified in the extract, respectively. However at pH 6.4, cooked Redclaw contained 73 positively identified aromatic compounds and did not show similar aroma profile to RCE extracted at the same pH condition. Major aromatic compounds were hydrocarbons (61 - 82%), comprising of alkanes (8 - 19%), alkenes (0.1- 1.8%), cyclic hydrocarbons (0.3 - 1.5%) and others hydrocarbons (49 - 64%). Butylated hydroxytoluene (BHT) was the dominant compound in all extracts and cooked Redclaw studied.